Clostridium ljungdahlii represents a microbial production platform based on syngas - Köpke, Michael; Held, Claudia; Hujer, Sandra; Liesegang, Heiko; Wiezer, Arnim; Wollherr, Antje; Ehrenreich, Armin; Liebl, Wolfgang; Gottschalk, Gerhard; Dürre, Peter; Demain, Arnold L. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Clostridium ljungdahlii is an anaerobic homoacetogen, able to ferment sugars, other organic compounds, or CO₂/H₂ and synthesis gas (CO/H₂). The latter feature makes it an interesting microbe for the biotech industry, as important bulk chemicals and proteins can be produced at the expense of CO₂, thus combining industrial needs with sustained reduction of CO and CO₂ in the atmosphere. Sequencing the complete genome of C. ljungdahlii revealed that it comprises 4,630,065 bp and is one of the largest clostridial genomes known to date. Experimental data and in silico comparisons revealed a third mode of anaerobic homoacetogenic metabolism. Unlike other organisms such as Moorella thermoacetica or Acetobacterium woodii, neither cytochromes nor sodium ions are involved in energy generation. Instead, an Rnf system is present, by which proton translocation can be performed. An electroporation procedure has been developed to transform the organism with plasmids bearing heterologous genes for butanol production. Successful expression of these genes could be demonstrated, leading to formation of the biofuel. Thus, C. ljungdahlii can be used as a unique microbial production platform based on synthesis gas and carbon dioxide/hydrogen mixtures.